Effects of sex, age, and season on the variation of blood analytes in a clinically healthy ex situ population of bottlenose dolphins (Tursiops spp.). (9th November 2020) - Nollens, Hendrik H.; Haney, Nylah J.; Stacy, Nicole I.; Robeck, Todd R.
Abstract: Background: A comprehensive evaluation of the effects of sex, age, and season on blood analytes in a robust population size of ex situ bottlenose dolphins ( Tursiops spp.) has not been investigated to date. Aim: To define the variation in hematological and biochemical analytes of dolphins due to sex, age, and season. Methods: 1, 426 blood samples collected from 156 clinically normal dolphins consisting of 59 males and 97 females in which 37 analytes were measured were retrospectively identified. The dolphins were categorized by age, sex, and season, and categories were compared. Results: About 23 (64%) analytes differed by age. The number of differences between adjacent age groups decreased with advancing age. MPV, glucose, BUN, globulins, GGT and Cl progressively increased with age, whereas Abs lymphs, total protein, ALP, CK and Ca progressively decreased with age. Three (8%) of analytes differed between sex, whereas 16 (44%) analytes differed by season. Female dolphins had higher median iron (33 µmol/L) than male dolphins (25 µmol/L). Female dolphins also had higher Abs lymphs and MCHC, but Abs lymphs and MCHC also differed between age and season, respectively. Sex inconsistently and relatively infrequently influences analytes. Delphinids of advancing age experience immune senescence and decreasing renal perfusion or clearance. Conclusions: These results demonstrate the importance of considering the influences of sex, age, and season on blood data, provide a baseline for accurate interpretation of clinicopathological analytes of delphinids in managed care, and will be useful for investigations into health, disease, and stressors of wild delphinids.